Kinetics of Plasma Cell‐Free DNA and Creatine Kinase in a Canine Model of Tissue Injury. (12th December 2017) - Wilson, I.J.; Burchell, R.K.; Worth, A.J.; Burton, S.E.; Gedye, K.R.; Clark, K.J.; Crosse, K.R.; Jack, M.; Odom, T.F.; De Grey, S.J.; McGlade, K.M.S.; Tomlin, S.C.; et al.
Abstract : Background: Cell‐free DNA (cfDNA) comprises short, double‐stranded circulating DNA sequences released from damaged cells. In people, cfDNA concentrations correlate well with disease severity and tissue damage. No reports are available regarding cfDNA kinetics in dogs. Objectives/Hypothesis: Cell‐free DNA will have a short biological half‐life and would be able to stratify mild, moderate, and severe tissue injury. Our study aims were to determine the kinetics and biological half‐life of cfDNA and to contrast them with those of creatine kinase (CK). Animals: Three groups of 10 dogs undergoing open ovariohysterectomy, surgery for cranial cruciate ligament rupture (CCLR), or hemilaminectomy. Methods: Plasma for cfDNA and CK analysis was collected at admission, at induction of anesthesia, postsurgery (time 0) and at 6, 12, 24, 36, 48, 60, and 72 hours after surgery. Results: The biological half‐life of plasma cfDNA and CK were 5.64 hours (95% confidence interval [CI 95], 4.36–7.98 hours) and 28.7 hours (CI95, 25.3–33.3 hours), respectively. In the hemilaminectomy group, cfDNA concentrations differed significantly from admission at 6–12 hours after surgery. Creatine kinase activity differed among the surgical groups and reached a peak 6 hours after surgery. In the ovariohysterectomy and CCLR groups, plasma CK activity 72 hours after surgery did not differ from admission activity of the ovariohysterectomy group. In contrast, in the hemilaminectomy group, plasma CK activity after 72 hours did not return to the ovariohysterectomy group admission activity. Conclusions and Clinical Importance: Plasma CK activity has a longer biological half‐life than previously thought. In contrast to plasma CK activity, cfDNA has a short half‐life and could be a useful marker for peracute severe tissue injury.